Pemberdayaan Peternak Milenial: Strategi dan Dampak: Empowering Millennial Farmers: Impact and Strategies - Afifudin, Fauzi Nur; Purwanto, Danang; Ghufronuddin, Ghufronuddin (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2023)
Ngargosari Village is undertaken in an effort to enhance community capabilities. This article aims to comprehend the implementation of empowerment strategies for millennial farmers and their impacts. The research methodology utilized is qualitative with a case study approach, employing data collection techniques through interviews and observations. This study showed that the implementation of empowerment strategies by Komunitas Ternak Lembu Mukti involves five main activities, namely plegung, regular arisan (rotating credit association), a savings and loan system for initial capital, the principle of 3 M (Self-Management, Financial Management, and time management), and the provision of land facilities by the village. These activities have had a positive impact on the members of the community and society at large, leading to enhanced livestock management skills, productivity, and welfare. This study concludes that the implementation of empowerment strategies for millennial farmers has yielded positive outcomes in terms of enhancing capabilities, productivity, and the welfare of the community. Furthermore, the strategies align with the principles of the ACTORS theory, as they grant communities the freedom to leverage local potential with the support of external actors as empowering agents. AbstrakPemberdayaan peternak milenial oleh Komunitas Ternak Lembu Mukti di Desa Ngargosari dilakukan sebagai upaya meningkatkan kemampuan masyarakat. Penelitian ini bertujuan untuk memahami penerapan strategi pemberdayaan peternak milenial serta dampaknya. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus dengan teknik penugumpulan data melalui wawancara dan observasi. Hasil penelitian menunjukkan bahwa penerapan strategi pemberdayaan oleh Komunitas Ternak Lembu Mukti melibatkan lima kegiatan utama, yaitu plegung, arisan rutin, sistem simpan pinjam untuk modal awal, prinsip 3 M (Manajemen Diri, Manajemen Keuangan, Manajemen Waktu), serta fasilitas lahan yang diberikan oleh desa. Kegiatan-kegiatan tersebut memberikan dampak positif pada anggota komunitas dan masyarakat, meningkatkan kemampuan mengelola ternak, produktivitas, dan kesejahteraan. Kajian ini menyimpulkan bahwa penerapan strategi pemberdayaan peternak milenial berdampak positif dalam meningkatkan kemampuan, produktivitas, dan kesejahteraan masyarakat serta sesuai dengan konsep teori ACTORS yang memberikan kebebasan kepada masyarakat untuk memanfaatkan potensi lokal dengan dukungan pihak lain sebagai pemberi daya.